2023
DOI: 10.1080/03007995.2023.2247323
|View full text |Cite|
|
Sign up to set email alerts
|

Development and validation of the COVID-19 Impact Scale in Australia

Kym Michelle McCormick,
Sneha Sethi,
Dandara Haag
et al.

Abstract: The R syntax for the simulation study and the simulated data (including simulation findings and plots) can be found at https://osf.io/ahuv3/. The datasets generated and/or analyzed during the current study are not publicly available. We do not have permission from the University of Adelaide Human Research Ethics Committee to publicly release the NDTIS 2021 dataset in either identifiable or de-identified form. The datasets are available from the corresponding author upon reasonable request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…This is all the more remarkable after acknowledging that public participation is repeatedly recommended in health disaster response literature" (Mouter, Hernandez, and Itten 2020) [p. 3] However, another corpus of 18 studies was identified that collected POD regarding COVID policy but did not explicitly use this data to inform COVID policymaking. (Angelou et al 2023;Behal, Davis, and Doering 2023;Fatihin et al 2022;Fitriansyah et al 2021;Hu et al 2021;Ifdil et al 2023;Kemper et al 2023;Kobayashi et al 2022;Loría-Rebolledo et al 2022;McCormick et al 2023;Morita et al 2023;Ntale and Ngoma 2021;Shakeel et al 2023;Sukhwal and Kankanhalli 2022;Suratnoaji, Nurhadi, and Arianto 2020;Veldwijk et al 2023;Yanuar Fahmi Pamungkas et al 2021;Yigitcanlar et al 2020) We therefore present commentary in two parts -first, analysis of the three studies meeting the review inclusion criteria; second, analysis of the 18 studies not explicitly connecting POD to policymaking. The rationale for including analysis of these 18 studies is to provide further practical insights on methods of POD data collection, given that very little research explicitly examined the influence of POD on public policymaking.…”
Section: "Government Driven Public Participation In Covid-19 Policyma...mentioning
confidence: 99%
“…This is all the more remarkable after acknowledging that public participation is repeatedly recommended in health disaster response literature" (Mouter, Hernandez, and Itten 2020) [p. 3] However, another corpus of 18 studies was identified that collected POD regarding COVID policy but did not explicitly use this data to inform COVID policymaking. (Angelou et al 2023;Behal, Davis, and Doering 2023;Fatihin et al 2022;Fitriansyah et al 2021;Hu et al 2021;Ifdil et al 2023;Kemper et al 2023;Kobayashi et al 2022;Loría-Rebolledo et al 2022;McCormick et al 2023;Morita et al 2023;Ntale and Ngoma 2021;Shakeel et al 2023;Sukhwal and Kankanhalli 2022;Suratnoaji, Nurhadi, and Arianto 2020;Veldwijk et al 2023;Yanuar Fahmi Pamungkas et al 2021;Yigitcanlar et al 2020) We therefore present commentary in two parts -first, analysis of the three studies meeting the review inclusion criteria; second, analysis of the 18 studies not explicitly connecting POD to policymaking. The rationale for including analysis of these 18 studies is to provide further practical insights on methods of POD data collection, given that very little research explicitly examined the influence of POD on public policymaking.…”
Section: "Government Driven Public Participation In Covid-19 Policyma...mentioning
confidence: 99%